2016
DOI: 10.1128/aem.03493-15
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analyses of the Autotrophic Fe(II)-Oxidizing, Nitrate-Reducing Enrichment Culture KS

Abstract: f Nitrate-dependent ferrous iron [Fe(II)] oxidation (NDFO) is a well-recognized chemolithotrophic pathway in anoxic sediments. The neutrophilic chemolithoautotrophic enrichment culture KS originally obtained from a freshwater sediment (K. L. Straub, M. Benz, B. Schink, and F. Widdel, Appl Environ Microbiol 62:1458 -1460, 1996) has been used as a model system to study NDFO. However, the primary Fe(II) oxidizer in this culture has not been isolated, despite extensive efforts to do so. Here, we present a metageno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
104
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 67 publications
6
104
1
Order By: Relevance
“…accounts for only 42% of the total community under autotrophic conditions (31). It has to be taken into account, however, that this culture has been transferred with a 10% inoculum for years while ours was transferred with a 1% inoculum, also for years (31). Previous studies found evidence that the remainder of the community in culture KS consists of strains that are not capable of autotrophic NRFeO but are heterotrophic nitrate reducers (10,30).…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…accounts for only 42% of the total community under autotrophic conditions (31). It has to be taken into account, however, that this culture has been transferred with a 10% inoculum for years while ours was transferred with a 1% inoculum, also for years (31). Previous studies found evidence that the remainder of the community in culture KS consists of strains that are not capable of autotrophic NRFeO but are heterotrophic nitrate reducers (10,30).…”
mentioning
confidence: 98%
“…This strain, here referred to as Gallionellaceae sp., was designated the autotrophic Fe(II) oxidizer in the culture (30). In the culture used in this study, it accounts for 96% of the total community under autotrophic growth conditions with Fe(II) and nitrate (31). In another version of culture KS from a different laboratory, which also has different community members, Gallionellaceae sp.…”
mentioning
confidence: 99%
See 3 more Smart Citations